Intestinal CD11b+ B Cells Ameliorate Colitis by Secreting Immunoglobulin A - Fu, Ying; Wang, Zhiming; Yu, Baichao; Lin, Yuli; Huang, Enyu; Liu, Ronghua; Zhao, Chujun; Lu, Mingfang; Xu, Wei; Liu, Hongchun; Liu, Yongzhong; Wang, Luman; et al. (Frontiers in Immunology, 2021)
The intestinal mucosal immune environment requires multiple immune cells to maintain homeostasis. Although intestinal B cells are among the most important immune cells, little is known about the mechanism that they employ to regulate immune homeostasis. In this study, we found that CD11b+ B cells significantly accumulated in the gut lamina propria and Peyer's patches in dextran sulfate sodium-induced colitis mouse models and patients with ulcerative colitis. Adoptive transfer of CD11b+ B cells, but not CD11b−/− B cells, effectively ameliorated colitis and exhibited therapeutic effects. Furthermore, CD11b+ B cells were found to produce higher levels of IgA than CD11b− B cells. CD11b deficiency in B cells dampened IgA production, resulting in loss of their ability to ameliorate colitis. Mechanistically, CD11b+ B cells express abundant TGF-β and TGF-β receptor II, as well as the highly activated phosphorylated Smad2/3 signaling pathway, consequently promoting the class switch to IgA. Collectively, our findings demonstrate that CD11b+ B cells are essential intestinal suppressive immune cells and the primary source of intestinal IgA, which plays an indispensable role in maintaining intestinal homeostasis.